2017
DOI: 10.1155/2017/5251313
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Mesenchymal Stem Cells in Spinal Cord Injury

Abstract: Spinal cord injury (SCI) represents one of the most complicated and heterogeneous pathological processes of central nervous system (CNS) impairments, which is still beyond functional regeneration. Transplantation of mesenchymal stem cells (MSCs) has been shown to promote the repair of the injured spinal cord tissues in animal models, and therefore, there is much interest in the clinical use of these cells. However, many questions which are essential to improve the therapy effects remain unanswered. For instanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 130 publications
(124 reference statements)
2
74
0
Order By: Relevance
“…), and in vivo differentiation has been questioned (Parr et al. ; Qu & Zhang, ). Some have even suggested that astrocytic differentiation of transplanted stem cells may be the default pathway (Kang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and in vivo differentiation has been questioned (Parr et al. ; Qu & Zhang, ). Some have even suggested that astrocytic differentiation of transplanted stem cells may be the default pathway (Kang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal differentiation of an autologous, easily accessible stem cell source has proved similarly challenging. For example, MSC differentiation towards a neuronal phenotype has proven inconsistent even in vitro (Scuteri et al 2011), and in vivo differentiation has been questioned (Parr et al 2008;Qu & Zhang, 2017). Some have even suggested that astrocytic differentiation of transplanted stem cells may be the default pathway (Kang et al 2012;Nakamura & Okano, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study demonstrate that application of AD-MSCs combined with fibrin matrix in a subacute period in rats provides significantly higher post-traumatic regeneration compared to a similar application BM-MSCs or DP-MSCs. Particularly, (1) restoration of locomotor activity and conduction along spinal axons, (2) reduction of post-traumatic cavitation and enhancing tissue retention, and (3) modulation of microglial and astroglial activation were found in rat model with AD-MSCs treatment. Besides, these data indicate that application of MSCs combined with fibrin matrix into the surface of spinal cord may be an effective and safest approach for delivering cells to the damaged area.…”
Section: Resultsmentioning
confidence: 99%
“…In this context, cell therapy is particularly well suited to address the multi‐factorial nature of secondary events following SCI, offering a neuroprotective and neuroregenerative competence, which confers a compelling widely investigated clinical potential (Assinck, Duncan, Hilton, Plemel, & Tetzlaff, ; Badner, Siddiqui, & Fehlings, ; Jin, Medress, Azad, Doulames, & Veeravagu, ). Among cell therapies, mesenchymal stem cell (MSC) transplantation is an attractive and promising approach for treating SCI favoured by its excellent safety profile and efficacy potential, as extensively reported in preclinical models and clinical trials of acute, subacute, and chronic SCI (Dasari, Veeravalli, & Dinh, ; Qu & Zhang, ; Shende & Subedi, ; Vawda & Fehlings, ). In particular, adipose MSCs (AMSCs) are easily obtained and have excellent expansion capacities, as well as a unique immunomodulatory and paracrine competence able to modulate many of the detrimental effects elicited after acute SCI (Mazini, Rochette, Amine, & Malka, ; Menezes et al, ; Takahashi et al, ).…”
Section: Introductionmentioning
confidence: 99%